2023
DOI: 10.1007/s40615-022-01508-y
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Racial Discrimination Experiences for Asian Americans During the COVID-19 Pandemic

Abstract: Background Asian Americans (AAs) are experiencing increased rates of anti-Asian racism during COVID-19. Experiences of racism, whether personal or collective, constitute stress and psychosocial trauma that negatively impact mental and physical health. Objectives Examine subgroup differences in rates of personal experience of discrimination and COVID-related collective racism and how each is associated with mental and physical health for AAs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
2
16
1
Order By: Relevance
“…Despite the change in administration, in 2021, Chinese American parents’ and youth’s heightened worries, fear, and concerns for their safety and well-being as racial minorities due to the Trump administration’s handling and responses to the COVID-19 pandemic did not decrease significantly from 2020. These findings support Tong et al’s [ 36 ] national survey results that Asian Americans perceived high levels of Asian hate online (a mean score of 3.72 on a 5-point scale) in 2020 and McGarity-Palmer et al’s [ 37 ] study that Chinese Americans rated a mean score of 3.75 on a 5-point scale measuring collective racism/Sinophobia in 2021.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the change in administration, in 2021, Chinese American parents’ and youth’s heightened worries, fear, and concerns for their safety and well-being as racial minorities due to the Trump administration’s handling and responses to the COVID-19 pandemic did not decrease significantly from 2020. These findings support Tong et al’s [ 36 ] national survey results that Asian Americans perceived high levels of Asian hate online (a mean score of 3.72 on a 5-point scale) in 2020 and McGarity-Palmer et al’s [ 37 ] study that Chinese Americans rated a mean score of 3.75 on a 5-point scale measuring collective racism/Sinophobia in 2021.…”
Section: Discussionsupporting
confidence: 85%
“…Even in the early months of the pandemic, there was concern that misinformation about COVID‐19 would ignite racist stereotypes about and discrimination against Asian Americans and that such behaviors would have a negative impact on the health of Asian Americans (Chen et al., 2020). Indeed, later research indicates that Asian Americans, particularly Chinese women, reported increased experiences of collective racism (McGarity‐Palmer et al., 2023), personal discrimination, and verbal and physical attacks (Hahm et al., 2021). Those who had personal experiences with discrimination were more likely to develop PTSD than those who did not experience discrimination directly (Hahm et al., 2021), but even those with indirect exposure showed increases in anxiety and depression (Cheah et al., 2020; Woo & Jun, 2022).…”
Section: The Dual Pandemicsmentioning
confidence: 99%
“…The survey was designed with the input of different national and local AA and NH/PI serving community organizations, and it was conducted from January 18, 2021 to April 9, 2021 recruiting AA and NH/PI adults living in the United States aged 18 years and older. Five Asian subgroups were specifically targeted during study recruitment: Chinese, Filipino, Korean, Vietnamese, and South Asian ethnicities (e.g., Bangladeshi, Indian, Pakistani; McGarity-Palmer, Saw, Sun, et al, 2023; McGarity-Palmer, Saw, Tsoh, et al, 2023). However, if individuals from other Asian ancestries completed the survey, they were not excluded from recruitment.…”
Section: Methodsmentioning
confidence: 99%